EBV‐miR‐BART12 accelerates migration and invasion in EBV‐associated cancer cells by targeting tubulin polymerization‐promoting protein 1. Issue 12 (23rd October 2020) - Wu, Yingfen; Wang, Dan; Wei, Fang; Xiong, Fang; Zhang, Shanshan; Gong, Zhaojian; Shi, Lei; Li, Xiayu; Xiang, Bo; Ma, Jian; Deng, Hao; He, Yi; et al.
Abstract: Epstein‐Barr virus (EBV) infection leads to cancers with an epithelial origin, such as nasopharyngeal cancer and gastric cancer, as well as multiple blood cell‐based malignant tumors, such as lymphoma. Interestingly, EBV is also the first virus found to carry genes encoding miRNAs. EBV encodes 25 types of pre‐miRNAs which are finally processed into 44 mature miRNAs. Most EBV‐encoded miRNAs were found to be involved in the occurrence and development of EBV‐related tumors. However, the function of EBV‐miR‐BART12 remains unclear. The findings of the current study revealed that EBV‐miR‐BART12 binds to the 3'UTR region of Tubulin Polymerization‐Promoting Protein 1 (TPPP1) mRNA and downregulates TPPP1, thereby promoting the invasion and migration of EBV‐related cancers, such as nasopharyngeal cancer and gastric cancer. The mechanism underlying this process was found to be the inhibition of TPPP1 by EBV‐miRNA‐BART12, which, in turn, inhibits the acetylation of α‐tubulin, and promotes the dynamic assembly of microtubules, remodels the cytoskeleton, and enhances the acetylation of β‐catenin. β‐catenin activates epithelial to mesenchymal transition (EMT). These two processes synergistically promote the invasion and metastasis of tumor cells. To the best of our knowledge, this is the first study to reveal the role of EBV‐miRNA‐BART12 in the development of EBV‐related tumors as well as the mechanism underlying this process, and suggests potential targets and strategies for the treatment of EBV‐related tumors.